2020
DOI: 10.1017/s1751731119002465
|View full text |Cite
|
Sign up to set email alerts
|

Saturated fat supplemented in the form of triglycerides decreased digestibility and reduced performance of dairy cows as compared to calcium salt of fatty acids

Abstract: The two most popular rumen-protected fatty acid supplements in dairy cow rations are calcium salts of palm oil fatty acid calcium salts of palm oil fatty acid (CSFA) and prilled saturated fatty acids (SFAs). The objectives of this study were to determine the effects of supplementing SFA in the form of triglycerides (TSFA), as compared to CSFA, on yields, efficiency and diet digestibility in high-yielding dairy cows. Twenty-eight (14 cows in each group) multiparous cows were fed a basal diet supplemented (on DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Other studies reported similar responses (de Souza et al, 2018;. In CSPF supplementation studies, a reduction in milk protein content with no change in milk protein yield is a very common observation (de Souza et al, 2018;Oyebade et al, 2020). We observed this effect in our study, which could have been the consequence of milk component dilutions, because CSPF increased milk yield, but had no effect on milk protein yield.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Other studies reported similar responses (de Souza et al, 2018;. In CSPF supplementation studies, a reduction in milk protein content with no change in milk protein yield is a very common observation (de Souza et al, 2018;Oyebade et al, 2020). We observed this effect in our study, which could have been the consequence of milk component dilutions, because CSPF increased milk yield, but had no effect on milk protein yield.…”
Section: Discussionsupporting
confidence: 80%
“…However, increasing the yields of both milk and milk fat resulted in no effect of CSPF on milk fat content. Other studies have reported that CSPF induced a dilution effect on milk fat content (Onetti and Grummer, 2004;Oyebade et al, 2020). Interestingly, the inclusion of CSPF did not affect BW, BW change, BCS, or energy output to maintenance.…”
Section: Discussionmentioning
confidence: 70%
“…Due to the very high melting point of these fats and their resulting low solubility, bacterial enzymes are unable to gain access to the binding of fatty acids to glycerol, which would pass to the lower digestive tract. [ 43 ]…”
Section: Resultsmentioning
confidence: 99%
“…A FibertecTM (Foss, Denmark) fiber analyzer was used to determine the amounts of acid detergent fiber (ADF) and neutral detergent fiber (NDF) using reagents that were reported by Van Soest et al [17] and added heat-stable amylase and sodium sulfite. The analyses of fatty acids (FA) profile of the HPS, FFW, and barely were performed using gas chromatography [18]. Table 2 shows the chemical composition of FFW and HPS.…”
Section: Preparation Of the Experimental Dietsmentioning
confidence: 99%